2023
DOI: 10.3389/fphar.2023.1135145
|View full text |Cite
|
Sign up to set email alerts
|

Therapeutic implications of current Janus kinase inhibitors as anti-COVID agents: A review

Abstract: Severe cases of COVID-19 are characterized by hyperinflammation induced by cytokine storm, ARDS leading to multiorgan failure and death. JAK-STAT signaling has been implicated in immunopathogenesis of COVID-19 infection under different stages such as viral entry, escaping innate immunity, replication, and subsequent inflammatory processes. Prompted by this fact and prior utilization as an immunomodulatory agent for several autoimmune, allergic, and inflammatory conditions, Jakinibs have been recognized as vali… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 172 publications
(198 reference statements)
1
6
0
Order By: Relevance
“…An effect was noticed in both IBV strains, though such an effect was not observed in the case of treatment with JAK-I inhibitor 420 092, and this is difficult to explain. Overall, our data indicated that inhibition of JAK-II decreases the IBV loads in macrophages, and our observation in this regard agrees with the observations made on other host viral models involving SARS-CoV-2, and Middle East respiratory syndrome coronavirus (MERS-CoV) [53,54].…”
Section: Discussionsupporting
confidence: 92%
“…An effect was noticed in both IBV strains, though such an effect was not observed in the case of treatment with JAK-I inhibitor 420 092, and this is difficult to explain. Overall, our data indicated that inhibition of JAK-II decreases the IBV loads in macrophages, and our observation in this regard agrees with the observations made on other host viral models involving SARS-CoV-2, and Middle East respiratory syndrome coronavirus (MERS-CoV) [53,54].…”
Section: Discussionsupporting
confidence: 92%
“…Despite the SARS-CoV-2 samples showing undetectable SARS-CoV-2 by RNA-scope, transcriptional profiling showed positive enrichment of SARS-CoV-2 related pathways in the SARS-CoV-2 samples, such as “SARS_COV_2_INFECTION”, and “SARS_COV_2_HOST_INTERACTIONS” from the Reactome database, as well as the Interferon Alpha Response pathway from the Hallmark database, which is a first-line immune response pathway that has been associated with SARS-CoV-2 infection (Figure 2d-f) 15 . These pathways were supported by increased expression of genes that have been associated with SARS-CoV-2, such as the inflammatory marker IFI16 16 , disease progression marker IFI27 17 , disease prognosticator B2M 18 , activation of Janus Kinases (i.e., JAK1 ), and expression of STAT3 19 (Figure 2 g-j). Notably, gene expression for these markers was elevated predominantly in the villous core stroma cell compartment, presumably stemming from the immune subpopulation within the stroma.…”
Section: Resultsmentioning
confidence: 86%
“… 15 These pathways were supported by increased expression of genes that have been associated with SARS‐CoV‐2, such as the inflammatory marker IFI16 , 16 disease progression marker IFI27 , 17 disease prognosticator B2M , 18 activation of Janus Kinases (i.e. JAK1 ), and expression of STAT3 19 (Figure 2g–j ). Notably, gene expression for these markers was elevated predominantly in the villous core stromal cell compartment, presumably stemming from the immune subpopulation within the stroma.…”
Section: Resultsmentioning
confidence: 89%